Acquisition of optical coherence tomography angiography metrics during hemodialysis procedures: A pilot study - Coppolino, Giuseppe; Bolignano, Davide; Presta, Pierangela; Ferrari, Fausto Francesco; Lionetti, Giovanna; Borselli, Massimiliano; Randazzo, Giorgio; Andreucci, Michele; Bonelli, Angelica; Errante, Antonietta; Campo, Leonardo; Mauro, Davide; et al. (Frontiers in Medicine, 2022)
Background and Aims: The observation of ocular microcirculation gives us an exceptional chance to directly evaluate in vivo the reactions of human circulation to stress stimuli. We run a pilot study to analyze optical coherence tomography angiography (OCT-A) metrics at determined time-points during a hemodialysis (HD) session to understand how these metrics gradually change and to evaluate possible correlations with patients‘ characteristics. Method: After the eligibility screening, 20 patients were included in the study. OCT-A parameters were collected at established time-points: before treatment (t0), at first hour (t1), at second hour (t2) and at third hour (t3), finally at the end of HD treatment (t4). Patients were finally shared in hypotensive group if they occurred in a hypotensive episode during subsequent month methods or no hypotensive group. Results: Overall, the majority of ocular parameters remained unchanged and comparable at dialysis end, a significant reduction being noticed at the end versus starting of HD only for DCP (whole, fovea and parafovea) and for central choroid thickness (CCT) (p<0.05). An overall trend during the session showed in general a decrease with a significance in particular for DCP (whole, fovea and parafovea) and for CCT (P=0.006). In the hypotension group SCP (fovea and parafovea) significantly increased comparing post vs. pre-dialysis values while CCT significantly decreased. Analyzing the trend during treatment only CCT maintained a significant trend (p for trend=0.002). In the no-hypotension group, neither pre vs. post analysis and trend analysis showed a statistical significance. Main achievement of our study was to measure, for the first time in literature, single parameters at different time-points of a HD session. As a result of this process we did not notice a brusque decreasing or increasing of OCT-A metrics but we can characterize the different effect of HD on the two distinct areas distinguishing ocular vessels: retinal and choroidal circulation. As interesting sub-analysis, Hypotensive group showed for CCT a decreasing trend with a difference statistically significant respect to the group with no hypotension maintaining a constant trend. In our opinion, these results suggest the role of autonomic system on vessel control in patients affected by uremia.